Properties of Atmospheric Pressure Ar Plasma Jet Depending on Treated Dielectric Material - Prysiazhnyi, Vadym [UNESP]; Ricci Castro, Alonso H. [UNESP]; Kostov, Konstantin G. [UNESP] (Springer Nature, 2017)
Atmospheric pressure plasma jet operated in argon was utilized to modify surfaces of glass, acrylic, and PTFE dielectrics. This paper describes the influence of the dielectric substrate on operation and properties of plasma. Two modes of operation (each of those have two patterns) were described. The transition from one mode to another, values of the dissipated power, and spreading of plasma over the dielectric surfaces strongly depended on the substrate material. Additionally, three methods of plasma spreading estimation were presented and discussed.
Keywords: Ar plasma jet; Atmospheric pressure plasma jet; Current patterns; Electrical characterization; Plasma spreading